Knowledge, attitude and at-risk behaviors for non-communicable diseases of public university students in Bangkok - Pookpun, Soracha; Rungsayatorn, Sheipsumon; Saratapun, Narumon (Kasetsart Journal of Social Sciences, 2017)
The objectives of this research were: 1) to investigate the level of knowledge, attitude, and at-risk behaviors for non-communicable diseases; and 2) to examine the relationship among knowledge, attitude, and at-risk behaviors for non-communicable diseases of public university students in Bangkok. A questionnaire was employed to gather data from 420 sampled students who were selected using multi-stage random sampling. Data were analyzed to acquire the percentage, mean, Pearson’s product moment correlation coefficient, and stepwise multiple regression, using a computer package. The findings revealed that more than two-thirds of the students were female with an average age of 19.83 years. About half of the students reported normal nutritional status and three-quarters of them had no underlying disease. The results showed that the knowledge and attitude of most students toward the prevention of non- communicable diseases were at a good level whereas at-risk behaviors for non-communicable diseases was at a moderate level. The relationship among knowledge, attitude, and at-risk behaviors for non-communicable diseases revealed that knowledge of noncommunicable diseases and attitude toward the prevention of noncommunicable diseases were positively correlated and statistically significant at the .01 level. The stepwise multiple regression showed that “avoid eating fast foods”, “avoid drinking cocktail”, “insomnia and nervousness are the symptoms of stress disorder”, “limit eating sweet fruits”, “exercise must be sweaty and make you tired”, “asthma is not caused by bacteria and is not communicable”, and “avoid eating instant food” were positively correlated with and influenced attitude toward the prevention of non- communicable diseases being statistically significant at the .001 level.